Meningkatkan Laba Melalui Networking - Aryani, Dwi Nita; Bunyamin, Bunyamin; Kadarusman, Kadarusman; Nurastuti, Nunung; Lating, Ali; Tjahjani, Fera; Hariadi, Sugeng; Zuchroh, Imama; Munfaqiroh, Siti; Setiawan, Setiawan; Murtiningtyas, Triana (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2023)
One of the company's goals is to increase profits. To increase profits can be done through increasing network relations (Networking). This community service is intended to provide insight into the importance of establishing networking so that business profits increase. Participants were given training and practice establishing relationships for 1 day. There were 20 MSME owners in Kampoeng Kajoetangan Malang who participated, then divided into 4 groups. Each group practices how to build relationships. From the training, the participants increased their knowledge and knew how to do or establish relationships. There are many ways to improve networking, namely attending training, attending exhibitions, social media, joining the community.